Restrained Eating Behavior in Free Living Adults: A Study in Delhi, India - Ifra Yusuf; Pulkit Mathur; Neha Bakshi (Journal of Integrated Health Sciences)
Introduction: Understanding the diverse factors for restricting foods is crucial, as it impacts the food choices and ultimately nutritional well-being. Objective: This study assessed the determinants of restrained eating behaviour among adults, exploring if fear/aversion was the reason for restraint. Materials and Methods: A total of 161 respondents aged 20–50 years who were active on social media platforms were recruited using snowball sampling. Body mass index (BMI) was calculated using self-reported height and weight. Standardized tools were used to analyze the cognitive restraint and food phobia using an online survey form. Results: Data showed higher restrained eating scores among 45% of the respondents. About 19% of the respondents were overweight and 36% were obese. There was a significant positive correlation of restrained eating with BMI. Females had significantly higher fear/aversion toward refined wheat flour products, fats, fried foods, bakery foods, sugar, and its products than males. Males had significantly higher fear/aversion for meat than females due to increased risk of infection. The number of restrained food items and level of fear significantly increased with age among males and females (P < 0.05). The major reasons identified for restraint eating were weight management, traditions/beliefs/customs, health concerns, and indigestion. Conclusion: Restraint eating and food aversions were significantly influenced by factors such as age, gender, BMI, with key motivation being weight management, cultural beliefs, and health concerns.